THE PREPARATION OF FUTURE GEOGRAPHY TEACHERS TO THE ORGANIZATION OF AN OUTDOOR PUPILS' ACTIVITY: MODEL'S SUBSTANTIATION - Dudka, Inna H. (Educological discourse, 2015)
This article deals with the model of training of future teachers of geography to extra-curricular activities of pupils, which is a set of interrelated elements of communication that ensure the formation of a system of qualities, knowledge and skills. The organizational and methodological conditions that ensure the preparation of future teachers of geography to extra-curricular activities of students are characterised. The model contains a set of tasks the implementation of which will contribute to achieving the required level of availability, namely: characterization of the nature of motivational, contextual, processual components of extracurricular activities of a geography teacher; identification and implementation of the content, forms and methods of preparation. Readinessof the future geography teachers to extracurricular activities as well as willingness to educational activities combines the same components, but some specific elements that provide the ability to extra-curricular activities of students exist. In this regard and due to the analysis of the structure of educational preparedness, it should be noted that the commitment to extracurricular activities on geography consists of motivation, content and process components. Special role in the implementation of the model of training of geographyteachers to extra-curricular activities of students plays a processual component, since it provides the acquisition of skills and development of skills of geography teacher to determine the purpose of extracurricular activities, organize extracurricular activities of students, predict outcome, to form an interest in conducting extra-curricular activities, analyze the results of their own extracurricular activities. According to the model of training of geographyteachers, theformation of the readiness to organize extracurricular activities of students occurs during learning psycho-pedagogical, methodological, professional disciplines and methods of teaching geography with following generalization and deepening in the course «Organization of extracurricular activity for pupils’in geography» and improving while teaching practices.